Treatment of Recurrent Dislocation of the Temporomandibular Joint with the Injection of Autologous Blood in Superior Joint Space with and without Pericapsular Tissue: An Experience at Tertiary Care Hospital of Peshawar - Aimen Mahmood Shah, Zakir Ullah Khan, Syeda Gulrukh Saba Shah, Zahid Sarfaraz Khan, Farkhanda Hina, Hurraia Zahid, Kaleem Ud Din, Irfan Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Recurrent TMJ (temporomandibular joint) dislocation is a condition characterized by frequent dislocation events. Recurrent TMJ dislocation may be treated using a variety of techniques, including conservative therapy and surgical treatments. Objective: The objective of the study was to assess the effectiveness of treatment of recurrent dislocation of the temporomandibular joint with injection of autologous blood in superior joint space with and without pericapsular tissue Methodology: The current study was prospective was carried out at the Kabir Medical College, Gandhara University, Peshawar for duration of one year from June 2021 to July 2022. The patients were categorized into group A and B, each having 50 patients. In group A patients the autologous blood was injected in superior joint space while in group B, autologous blood was injected in pericapsular tissue. The average reduction in mouth opening was recorded in both the groups. All the data analysis was performed by using IBM SPSS version 23. Results: In group A patients, a mean (±sd) decrease in mouth opening of 3.30 (0.77) mm was observed (p=0.001) while a mean (±sd) decrease in mouth opening of 4.56 (0.72) mm was observed in group B patients (p=0.001). Dislocation recurrence was observed in 4 (57.14%) patients in group A while in group B, dislocation recurrence was observed in 3 (42.86%) patients (p=0.001). Conclusion: Our study concludes that management of recurrent dislocation of TMJ with injection of autologous blood was safe, efficient, simple and economic procedure. Patients with recurrent TMJ dislocation should be encouraged to use autologous blood injection for their treatment. Keywords: Recurrent; Temporomandibular joint dislocation; Autologous blood injection